25 Diagnostic Value of Myocardial Blood Flow Imaging in Patients with Ischaemia and Non-Obstructive Coronary Arteries. (28th January 2023) - Corcoran, David; Bradley, Conor; Ford, Thomas J; Stanley, Bethany; Hsu, Li-Yueh; Orchard, Vanessa; Campbell, Ross; McEntegart, Margaret; Rocchiccioli, Paul; Watkins, Stuart; Good, Richard; Radjenovic, Aleksandra; et al.
Abstract : Funding: This work was supported by the British Heart Foundation (grant numbers: PG/17/2532884; RE/13/5/30177; RE/18/6134217). The trial sponsor is the Golden Jubilee Research Foundation. The British Heart Foundation has supported DC through a research fellowship (FS/14/15/30661). AEA and LH are supported by intramural funding from the National Heart Lung and Blood Institute. Disclosures: C.B. is employed by the University of Glasgow, which holds consultancy and research agreements with companies that have commercial interests in the diagnosis and treatment of angina. The companies include Abbott Vascular, AstraZeneca, Boehringer Ingelheim, GSK, HeartFlow, Neovasc, Novartis, Siemens Healthcare, and Valo Health. K.G.O. has received consultant and speaker fees from Abbott Vascular and Volcano Corporation which manufacture pressure wires. He is an employee of Biosensors International. S.W. has worked as a consultant for Abbott Vascular. A.E.A. holds US government Cooperative Research and Development Agreements with Siemens, Bayer, and Circle CVI. A.E.A. and L.H. have pending patents and invention reports related to perfusion quantification. None of these companies have had any involvement with this study. None of the other authors have any potential conflicts of interest. Acknowledgements: We thank the staff and patients who supported this study and the British Heart Foundation. Aims: Patients with suspected ischaemic symptoms but no obstructive coronary arteries (INOCA), have uncertain management and suboptimal clinical outcomes. We prospectively investigated the associations between multiparametric CMR imaging, clinical endotypes, and health status, in patients with suspected INOCA. Methods and results: Patients were assessed using functional coronary angiography including guidewire-based measurement of coronary flow reserve, index of microcirculatory resistance, and acetylcholine vasoreactivity testing. CMR imaging included native-T1 mapping, stress perfusion myocardial blood flow quantification, and late gadolinium enhancement. The primary outcome was the association between reduced myocardial perfusion reserve (MPR <2.0) and INOCA endotypes as classified by invasive coronary function testing. Patient reported outcome measures were recorded independent of the CMR findings. One hundred and fifty-one patients underwent functional coronary angiography, 124 underwent CMR, and 108(71% female, age 60±10 years) had complete data. The endotypes were: microvascular angina n=57(53%), vasospastic angina n=19(18%), mixed n=18(17%), non-cardiac chest pain n=14(13%). MPR was associated with angina severity (0.03 unit increase in MPR per 10 unit increase in SAQ summary score, 95% confidence interval (CI) 0.00, 0.07, p=0.048) and quality of life (0.04 unit increase in MPR per 0.1 unit increase in EQ-5D score, 95% CI 0.01, 0.06, p=0.007). Reduced MPR occurred in 79(73%) patients. MBF did not discriminate between endotypes. Myocardial scar occurred in 10(9%) patients (n=5 myocardial infarction; n=5 non-ischaemic pattern). Conclusions: MPR correlated with angina severity and health-related quality of life and reduced MPR and myocardial scar were prevalent. CMR appears to be diagnostically useful in symptomatic patients with no obstructive CAD. Clinical Trial Registration: ClinicalTrials.gov Identifier: NCT03193294